Consensus Guidelines for the Use of Vosoritide in Children with Achondroplasia in Australia - Louise Tofts; Penny Ireland; Tracy Tate; Supriya Raj; Theresa Carroll; Craig F. Munns; Stephen Knipe; Katherine Langdon; Lesley McGregor; Fiona McKenzie; Andreas Zankl; Ravi Savarirayan (MDPI AG, 2024)
Background: Achondroplasia, the most prevalent skeletal dysplasia, stems from a functional mutation in the fibroblast growth factor receptor 3 gene, leading to growth impairment. This condition presents multifaceted medical, functional and psychosocial challenges throughout childhood, adolescence and adulthood. Current management strategies aim to minimise medical complications, optimise functional capabilities and provide comprehensive supportive care. Vosoritide (trade name: VOXZOGO®, BioMarin Pharmaceuticals) is the first disease-modifying pharmaceutical treatment approved for the management of patients with achondroplasia and became available in Australia in May 2023. Methods: Standardised clinical guidelines for its optimal use are not yet widely available. To address this gap, a multidisciplinary Australian Vosoritide Working Group, comprising 12 experts with experience in achondroplasia management from across Australia, developed recommendations to guide the use of vosoritide in clinical practice. Results: The recommendations, which are expert opinions of the Australian Vosoritide Working Group, aim to (i) standardise the use of vosoritide across Australia, (ii) support the safe clinical rollout of vosoritide and (iii) support universal access. Conclusions: These recommendations have been developed for healthcare professionals and institutions that are engaged in using vosoritide in the management of achondroplasia and will be revised using a formal framework for clinical guideline development once more evidence is available.